Curcumin Enhances Antimigration of Pentagamavunon-1 by Suppressing MMP-2 and MMP-9 Expression in Triple-Negative (4T1) and Luminal A (T47D) Breast Cancer Cells - Desty Restia Rahmawati; Edy Meiyanto; Riris Istighfari Jenie; Arief Nurrochmad (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Breast cancer remains the leading cause of cancer death worldwide. Migration and invasion of cancer cells are still crucial stages in the metastasis process, highlighting the urgent need for treatments that target both proliferation and metastatic progression. Curcumin and its synthetic analogue, pentagamavunon (PGV)-1, exhibit antiproliferative effects in breast cancer cells. However, the effects of combining curcumin and PGV-1 on cancer cell migration have not yet been explored. Therefore, this study was conducted to examine the antimigratory effects of curcumin and PGV-1 combination on 4T1 and T47D breast cancer cells.METHODS: Cytotoxicity effects of curcumin and PGV-1 were examined using an MTT assay to determine their effects on 4T1 and T47D cell viability. The antimigration activity was assessed using a scratch wound healing assay by measuring the closure of artificially created wounds on monolayer cells. Expression of matrix metalloproteinases (MMPs) that play a crucial role in cancer cell migration was analyzed using gelatin zymography to measure their enzymatic activities.RESULTS: The IC50 of PGV-1 and curcumin were 4.88 μM and 37.62 μM in 4T1 cells and 3.16 μM and 23.15 μM in T47D cells, respectively. Furthermore, combination of PGV-1 and curcumin effectively inhibited 4T1 and T47D cell migration. PGV-1 (0.5–2 μM) demonstrated superior antimigratory activity compared to curcumin (5–20 μM) by suppressing MMP-2 and MMP-9 expression in both cell lines. Significantly, curcumin was shown to synergistically enhance the antimigratory effects of PGV-1, leading to a further decrease in MMP-2 and MMP-9 expression. CONCLUSION: The combination of PGV-1 and curcumin may provide a promising antimigratory agent, potentially leading to enhanced antimetastatic strategies and more efficacious treatments for triple-negative and luminal breast cancer patients.KEYWORDS: antimigration, curcumin, luminal breast cancer, MMP-2, MMP-9, pentagamavunon-1, triple-negative breast cancer